Validation of the Itch Severity Item as a Measurement Tool for Pruritus in Patients with Psoriasis: Results from a Phase 3 Tofacitinib Program - Sonja Ständer; Thomas Luger; Joseph C. Cappelleri; Andrew G. Bushmakin; Carla Mamolo; Michael A. Zielinski; Anna M Tallman; Gil Yosipovitch (Medical Journals Sweden, 2017)
Tofacitinib is an oral Janus kinase inhibitor. This post-hoc analysis aimed to investigate the psychometric properties of the Itch Severity Item (ISI), a numeric rating scale from 0 (no itching) to 10 (worst possible itching) for pruritus in psoriasis, and review the effect of tofacitinib on pruritus in patients with psoriasis participating in Phase 3 studies (N = 3,641). The ISI showed high test-retest reliability (intra-class correlation coefficient: 0.84). The clinically important difference was defined as a 1.48-point change, using Patient Global Assessment as an anchor. Mean changes from baseline in ISI scores with tofacitinib were significantly greater than placebo by Day 2 and exceeded the clinically important difference by Week 4 and Week 2 for tofacitinib 5 and 10 mg twice daily, respectively. The sound psychometric properties of the ISI as an assessment tool for pruritus in psoriasis were confirmed. Tofacitinib provided clinically meaningful improvements in psoriatic pruritus versus placebo.